Students' Motivation to Attend Al-Qur'an Learning on Telegram - Widyastri, Sri (Lembaga Pendidikan Hikmatun Najah Blora, 2024)
This research aims to unravel the motivation of participants from various countries in memorizing the Qur'an on social media, especially on Telegram. One of the most popular social media in the Arab world is a telegram which is used as a medium for learning the Qur'an. ØªØ³Ù…ÙŠØ¹ ØØ± Ø±ÙÙŠÙ‚Ø§Øª Ø§Ù„Ø®ÙŠØ± and ØªØ³Ù…ÙŠØ¹ ÙˆØªØ¹Ø§ÙˆÙ†ÙˆÙ† Ø¨ÙŠÙ† Ø§Ù„Ø§Ø®ÙˆØ§Øª are halaqah's of memorizing the Al-Qur'an specifically for women who are the objects of this research. The theory used in this study is the theory of the ARCS Model to understand and analyze the phenomenon of motivation for learning the Qur'an on social media. The research method used was qualitative with case studies in the two groups by interviewing several female students. Data collection techniques were carried out through interviews, observation, and documentation. The results showed that the participants gave attention to memorizing the Qur'an due to cultural motives which have become a hereditary tradition, not something new or unique. There are elements relevant to memorizing the Al-Qur'an with daily life that is a need for the soul, there is a feeling of wanting to be calm, happy, feeling safe and protected from danger so that it is motivated to interact with the Al-Qur'an. Element Confidence that is, students believe memorizing the Qur'an can motivate them to succeed in the hereafter, not only in the world. Elements satisfaction that is, the participants have a feeling of satisfaction from within themselves in memorizing the Qur'an. The novelty value of this research is the importance of motivation and its elements in memorizing the Qur'an to achieve the pleasure of Allah SWT. The importance of using telegram media from any country in collaborating to transmit the Qur'an towards quality memorization. Motivation to memorize the Qur'an is an important indicator in the religious traditions of Arab women. It is a traditional practice that has been passed down from previous generations to the present so that memorizing the Qur'an is not something unique and new but a sure way to achieve true happiness not happiness in the world alone.